PELAYANAN PEMERINTAH KOTA PEKANBARU DALAM PENGADAAN PERUMAHAN RAKYAT DAN KAWASAN PEMUKIMAN TAHUN 2017 - Ichsan, Astaka; M, Erman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The problems of public housing and residential areas as a government affair compulsory basic services organized by the Pekanbaru City Government have practically been implemented, but there are still various problems that remain unresolved.This study aims to determine the Pekanbaru City Government's actions in implementing compulsory affairs in the field of public housing and residential areas and to determine the pattern of integrating interests between the government, the private sector and the community in developing housing and residential areas in Pekanbaru City. Primary information sources (informants) are determined by purposive sampling and the necessary data are collected by interview techniques and literature study.From the results of this study it is known that the Pekanbaru City Government's actions in implementing compulsory affairs in the field of public housing and residential areas are carried out by meeting the needs of the House as one of the basic human needs in the framework of enhancing and equitable distribution of people's welfare, but in its implementation there are still MBRs that have not yet have Residential (Houses) and Budget Allocation that have not led to the need for RLH for MBR, Realizing decent housing and settlements in a healthy, safe, harmonious, and orderly environment. Where what happens is the granting of residential area permits that do not pay attention to environmental aspects and the development of residential and residential areas, in fact many do not pay attention to environmental aspects such as water catchment area closure, river flow and land contour changes, give direction to regional growth and population rationale that will be rational but the Selective Office of the City of Pekanbaru has not been selective in issuing permits to build buildings and support development in the economic, social, cultural and other fields that can be done by providing housing in urban areas and carried out in stages and adjusted to the ability of citizens.In addition, the integration of interests between the Government, Private Sector and the Community in the Development of Housing and Settlement Areas in the City of Pekanbaru is carried out by efforts to implement the Standardization of Housing Development, Supervision and control of housing development and implement improvements in housing quality.